Annotation: Methodological and Conceptual Issues in Research on Childhood Resilience - Luthar, Suniya S. (J Child Psychol Psychiatry, 1993)
Recent advances in research on childhood resilience have yielded valuable insights on protective processes in adjustment. At the same time, however, as with any growing discipline, the rapid accrual of data has led to the identification of additional important questions, many of which are currently inadequately resolved. The focus of this paper is on salient methodological and conceptual issues that merit further scrutiny in research on resilience. The discussion focuses in turn on definitions of competence, measurement of risk, terminology used to describe protective mechanisms, main effect and interaction effect models of resilience, and processes underlying “buffering” or “moderating” effects.